Real Time Video Surveillance System for Fire and Smoke Detection Based on Wavelet Transform. - Mohammed, Tahsin A.; Mohammed, Aree A. (Sulaimani Journal for Pure and Applied Sciences, 2017)
Fire detection processing technique for Video Surveillance Systems (VSS) has attracted the interest of a lot of researchers because of its crucial value in various applications in our daily life. In this research work, a real time video surveillance system for fire detection based on wavelet transforms is proposed. It aims to design and implement fire detection in a spatial and wavelet domain domain. The input video is first extracted into frames and then the motion detection algorithm for the change detection is applied to separate moving objects from the static objects. Test results of the proposed fire and smoke detection methods at different distance from one to ten meters indicate that the accuracy of the system for frames with performing contour algorithm (average accuracy for (1-10) meter is equal to (99.46%). On the other hand, in a frequency domain the system has a better performance for detecting energy of fire than a smoke.
Keywords: Fire detection; Wavelet technique; Contour; Accuracy; Energy